A literatura ouve: proposições práticas para a formação literária do aluno surdo - Amaral, Elissiane Aparecida Zen do (2020)
The issue of inclusive education has been widespread in the country in recent decades, especially with regard to the deaf student. One of the challenges of the deaf is the learning of the written modality of the Portuguese language and, in particular, the reading and understanding of literary texts. In this direction, this research started with the following guiding question: Can literature and the exposure to literary texts help deaf students in the field of the written Portuguese language or in their better understanding? In order to find the answer(s) to this question, we have outlined, as a general objective, to provide and provoke the taste of learning in the deaf student, opportunizing the socialization, communication and interpretation of the world around him, having in literature a way of access to such learning. This research, in methodological terms, is characterized as an action research. Theoretically, it is based on the discussions of Historical-Cultural Psychology, especially in relation to language and the phases of development of the child, and on the discussions on literacy and literary literature. The study proposed the elaboration of didactic-pedagogical activities that aim at giving deaf students the opportunity to have contact with literature, either through their natural language (LIBRAS) or through their additional language (LP). As a result of this research process, we understand that it will be possible, from the development of the proposed activities, to provide deaf students with a better understanding of the Portuguese language in its written form.